Analisis Indikator Pendidikan: Partisipasi Pendidikan di Indonesia Periode 1994-2018 - Fatah, Abdul; Suhaili, Muhammad; Farida, Isna (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2021)
This study aims to examine indicators of education in Indonesia based on the School Participation Rate (SPR), Rough Participation Rate (RPR), and Pure Participation Rate (PPR). This research used quantitative methods. The type of data used was secondary data obtained from the Central Statistics Agency (CSA) during the 1994-2018 period. The instrument used by BPS to collect data was a questionnaire through the National Survey and Census program (Susenas). The population involved in this study was all Indonesians based on age and education level. The data were processed using quantitative statistics with explorative descriptive analysis. The results showed that the SPR, RPR, and PPR in Indonesia based on age and level of education had an increasing trend. However, based on the average SPR, RPR, and PPR scores, educational participation has decreased with increasing age and level of education taken.